2007
DOI: 10.1562/0031-8655(2003)0770319datotf2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Dose and Timing of the First Light Fraction in Two-fold Illumination Schemes for Topical ALA-mediated Photodynamic Therapy of Hairless Mouse Skin¶

Abstract: A fractionated illumination scheme in which a cumulative fluence of 100 J cm 22 is delivered in two equal light fractions separated by a dark interval of 2 h has been shown to considerably increase the efficacy of 5-aminolevulinic acid (ALA)-photodynamic therapy (PDT). The efficacy of such a scheme is further increased if the fluence of the first light fraction is reduced to 5 J cm 22 . We have investigated the relationship between the PDT response and the kinetics of protoporphyrin IX (PpIX) fluorescence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 12 publications
3
38
1
Order By: Relevance
“…In addition to enhanced tumor cell kill due to hypoxia from vascular damage, the vascular responses may also be part of the mechanism behind the success of light‐fractionated PDT. For ALA‐PDT, light fractionation has proven beneficial in both preclinical and clinical studies . We hypothesize that the vascular endothelium synthesizes a small but relevant amount of PpIX which makes it vulnerable to a second illumination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enhanced tumor cell kill due to hypoxia from vascular damage, the vascular responses may also be part of the mechanism behind the success of light‐fractionated PDT. For ALA‐PDT, light fractionation has proven beneficial in both preclinical and clinical studies . We hypothesize that the vascular endothelium synthesizes a small but relevant amount of PpIX which makes it vulnerable to a second illumination.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has investigated the role of light fractionation in the response of tissues to ALA-PDT in animal 6,7 and clinical studies. 8,9 In a randomized comparative study of the response of superficial basal cell carcinoma (sBCC) to ALA-PDT, our group showed a significantly higher complete response rate at 1 year (n=476) (P = .002) using a 2-fold illumination scheme (20 ϩ 80 J/cm 2 ) with a 2-hour dark interval compared with a single illumination (75 J/cm 2 ).…”
mentioning
confidence: 99%
“…Our group has shown that there is no difference in response of sBCC to ALA-PDT using these sources and light fractionation. 9 The rationale for choosing these illumination schemes-in particular the reason we used unequal total light fluences-is based on extensive work in preclinical models 6,7 and our group's demonstrated results in the treatment of sBCC. 8,9 These factors are discussed at length by de Haas et al 9 Patients were examined after 4 weeks and then at 3-month intervals.…”
mentioning
confidence: 99%
“…Results of these studies show that fractionated PDT results in significantly higher responses compared with PDT done with a single illumination 8,9 . Studies have also shown the importance of the time interval between ALA application and the first light fraction and its relation to the synthesis of PpIX 10 . Besides, the influence of the fluence (rate) of the individual light fractions 10,11 and, importantly, the time interval between light fractions has been shown to be critical 12 .…”
Section: Discussionmentioning
confidence: 96%